SPE Annual Technical Conference and Exhibition 1986
DOI: 10.2118/15389-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mixing During Two-Phase, Steady-State Laboratory Displacements in Sandstone Cores

Abstract: were linear functions of velocity at any given saturation.Brine dispersion coefficients were This paper examines the changes in fluid distriindistinguishable from those obtained in stable, butions and the mixing that occurs in immiscible single-phase diap?ncementa on the same cG.e. Oil phases flowing in a porous medium with changes in phase dispersion coefficients were, in general, phase saturations and flow rates. We report experi-greater than those for the brine phase, but decreased mental results for steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The dead-end pores contribute about 34%−51% of the pore space of the reservoir rocks, which causes significant oil trapping in these pore constrictions. 41 A heterogeneous porous medium geometry is taken from Keller et al, 39 and a fracture has been created horizontally in the middle of the porous medium to understand the severity of oil trapping. The total void space present in the porous medium is 1.18 × 10 −7 m 2 .…”
Section: Simulation Setupmentioning
confidence: 99%
“…The dead-end pores contribute about 34%−51% of the pore space of the reservoir rocks, which causes significant oil trapping in these pore constrictions. 41 A heterogeneous porous medium geometry is taken from Keller et al, 39 and a fracture has been created horizontally in the middle of the porous medium to understand the severity of oil trapping. The total void space present in the porous medium is 1.18 × 10 −7 m 2 .…”
Section: Simulation Setupmentioning
confidence: 99%
“…The effect of the absolute value of viscosity is neglected. Shown in Figs.5.4.7 and 5.4.8 are effluent concentration profiles for Berea and Rock Creek sandstones, respectively, given by Bretz et al 34. On the left side of each figure is the water phase dispersion curve, and on the right side is the oil phase dispersion curve.…”
Section: Dependence Of S-shaped Curve On Fluid Viscositymentioning
confidence: 99%
“…Using this model, Bretz et al. (1986) and Bretz and Orr (1987) found that the fraction of dead‐end pores in porous media can be up to 34%, 42%, and 51% for certain Berea sandstone, Rock Creek sandstone, and San Andres carbonate rocks, respectively. Later, similar models were developed for both miscible and immiscible displacements at different scenarios (Babaei & Islam, 2020; Bai et al., 1995; Karadimitriou et al., 2016; Piquemal, 1993; Salter & Mohanty, 1982; van Genuchten & Wierenga, 1976).…”
Section: Introductionmentioning
confidence: 99%